Dynamic interface charge governing the current–voltage hysteresis in perovskite solar cells1. Issue 15 (21st April 2015) - Zhang, Huimin; Liang, Chunjun; Zhao, Yong; Sun, Mengjie; Liu, Hong; Liang, Jingjing; Li, Dan; Zhang, Fujun; He, Zhiqun
<x xml:space="preserve">Abstract</x> Since interface charge changes band bending and thus influences photocurrent, its dynamics governs the current–voltage hysteresis.